2004
DOI: 10.1111/j.1365-2672.2004.02224.x
|View full text |Cite
|
Sign up to set email alerts
|

RAPID detection and quantification of E. coli O157/O26/O111 in minced beef by real-time PCR

Abstract: The enrichment, isolation and detection procedures used in this study provide a rapid routine-based molecular method for the detection and differentiation of E. coli O26, O111 and O157 from minced meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…As raw ground beef can be undercooked, E. coli O157:H7 was declared an adulterant (as defined in 9 CFR x301.2) in this product; (Anonymous, 1999;Donnenberg and Whittam, 2001) and there is interest in identifying the occurrence of other groups of species that elaborate these toxins (Karmali et al, 1985;Jaeger and Acheson, 2000;Bosilevac et al, 2007;Eblen, 2007) as they, too, have been shown to have public health impact (Neill et al, 1985;Murphy et al, 2005) and occur in beef (O'Brien et al, 1982;O'Hanlon et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…As raw ground beef can be undercooked, E. coli O157:H7 was declared an adulterant (as defined in 9 CFR x301.2) in this product; (Anonymous, 1999;Donnenberg and Whittam, 2001) and there is interest in identifying the occurrence of other groups of species that elaborate these toxins (Karmali et al, 1985;Jaeger and Acheson, 2000;Bosilevac et al, 2007;Eblen, 2007) as they, too, have been shown to have public health impact (Neill et al, 1985;Murphy et al, 2005) and occur in beef (O'Brien et al, 1982;O'Hanlon et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Hence, some false-negative results could be obtained after the IMS analysis, for which only 6 h of incubation is recommended (ISO EN 16654). For an enrichment with 6 h of incubation before detection by PCR, some false-negative results could be also obtained (20,34).…”
Section: Vol 72 2006mentioning
confidence: 99%
“…This is detrimental for reliable quantification. We demonstrated above that most of the primers and probes described in the literature for STEC detection or quantification [17,22,23,24,25,26,27,28,29,30,31] contained several mismatches when aligned to gene sequences of the different variants of stx1 , stx2 and eae . This implies that amplification is not optimal for some gene variants only.…”
Section: Discussionmentioning
confidence: 96%
“…Subtypes of stx were denominated according to the subtyping nomenclature established at the 7th International Symposium on Shiga Toxin (Verocytotoxin)-Producing Escherichia coli Infections (Buenos Aires, 10–13 May, 2009). Various primer-probe combinations for stx1 , stx2 and eae from the literature [17,22,23,24,25,26,27,28,29,30,31,32,33] and newly designed primers and probes using Primer Express 2.0 (Applied Biosystems, Foster City, CA, US), were aligned to the local database. The combinations that resulted in the fewest mismatches (≤2 in a primer, ≤1 in a probe) for the aforementioned subtypes (except stx2f ) were selected.…”
Section: Methodsmentioning
confidence: 99%